The effects of three different recovery methods on cycle performance in the heat - de Pauw, K.; Roelands, B.; Meeusen, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Although the scientific information on recovery and cycle performance is abundant, little is known about the influence of recovery between consecutive cycle performances in the heat. Therefore the aim of this study is to determine the influence of active recovery (AR), passive rest (PR) and cold water immersion (CWI) on repeated simulated time trial performance in the heat. Methods: Nine trained male subjects (age: 22.7 ± 3.4 yrs; VO2max: 62.1 ± 5.3 ml.min-1.kg-1) participated in this randomized crossover study, and they performed a max test, familiarization trial and 3 experimental trials interspersed by a 6-d rest period. Each trial consisted of two cycle performances in a warm environment (30°C; 45-55%) separated by one hour. The first cycle performance included a 60 min constant load trial (at 55% Wmax), followed by a 30 min simulated time trial (TT1). The second cycle performance comprised a 12 min simulated time trial (TT2) that started at 85% Wmax. Immediately after TT1 AR (cycling at 80W), PR or CWI (water temperature set at 15°C, subjects immersed until sternum) was applied for 15 minutes. Outcomes: TT performance was used as primary outcome measure. Heart frequency (HF), blood lactate concentration [BLa], rating of perceived exertion (RPE), thermal comfort (TC), rectal temperature (Trect) and skin temperatures (Tskin) were measured. Results: Compared to PR (13.23 ± 1.25 min) and AR (13.27 ± 1.05 min), CWI (12.71 ± 0.71 min) resulted in a 30 seconds faster TT2. It is noteworthy that after CWI [BLa] was significantly higher during TT2 compared to PR at 6 min (p=0.011), and compared to PR and AR at 9 min (p=0.021, p=0.044 respectively). HF on the other hand was significantly lower compared to AR at 0 min (p=0.000) and 3 min (p=0.002), and compared to PR at 0 min (p=0.000) and 6 min (p=0.038). CWI significantly reduced Trect and Tskin during the recovery period and lower Trect and Tskin were sustained during rest and TT2. Discussion/Conclusion: In a previous study from our lab (De Pauw et al, 2011) we observed no differences in a second cycle performance after applying different recovery interventions (PR, upper leg cooling, AR, AR + upper leg cooling). An interesting finding was the faster decrease of [BLa] during AR combined with upper leg cooling (15°C). In this study we immersed subjects until the chest and found better TT2 performance that can be contributed to an increased heat storage capacity. Subjects performed better during TT2 with a lower HF and a higher [BLa]. Thus, the present study provides evidence for the ergogenic effect of CWI as a recovery intervention between two exercise bouts in the heat.